Effect of retroviral proteinase inhibitors on Mason-Pfizer monkey virus maturation and transmembrane glycoprotein cleavage. - Sommerfelt, M A (J Virol, 1992)
Mason-Pfizer monkey virus (M-PMV) is the prototype type D retrovirus which preassembles immature intracytoplasmic type A particles within the infected cell cytoplasm. Intracytoplasmic type A particles are composed of uncleaved polyprotein precursors which upon release are cleaved by the viral proteinase to their constituent mature proteins. This results in a morphological change in the virion described as maturation. We have investigated the role of the viral proteinase in virus maturation and infectivity by inhibiting the function of the enzyme through mutagenesis of the proteinase gene and by using peptide inhibitors originally designed to block human immunodeficiency virus type 1 proteinase activity. Mutation of the active-site aspartic acid, Asp-26, to asparagine abrogated the activity of the M-PMV proteinase but did not affect the assembly of noninfectious, immature virus particles. In mutant virions, the transmembrane glycoprotein (TM) of M-PMV, initially synthesized as a cell-associated gp22, is not cleaved to gp20, as is observed with wild-type virions. This demonstrates that the viral proteinase is responsible for this cleavage event. Hydroxyethylene isostere human immunodeficiency virus type 1 proteinase inhibitors were shown to block M-PMV proteinase cleavage of the TM glycoprotein and Gag-containing precursors in a dose-dependent manner. The TM cleavage event was more sensitive than cleavage of the Gag precursors to inhibition. The infectivity of treated particles was reduced significantly, but experiments showed that inhibition of precursor and TM cleavage may be at least partially reversible. These results demonstrate that the M-PMV aspartyl proteinase is activated in released virions and that the hydroxyethylene isostere proteinase inhibitors used in this study exhibit a broad spectrum of antiretroviral activity. IMAGES: